2012
DOI: 10.1038/jcbfm.2012.52
|View full text |Cite
|
Sign up to set email alerts
|

CD36 is Involved in Astrocyte Activation and Astroglial Scar Formation

Abstract: Inflammation is an essential component for glial scar formation. However, the upstream mediator(s) that triggers the process has not been identified. Previously, we showed that the expression of CD36, an inflammatory mediator, occurs in a subset of astcotyes in the peri-infarct area where the glial scar forms. This study investigates a role for CD36 in astrocyte activation and glial scar formation in stroke. We observed that the expression of CD36 and glial fibrillary acidic protein (GFAP) coincided in control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 45 publications
(72 reference statements)
5
67
1
Order By: Relevance
“…In particular, CD36, a class B scavenger receptor, has been implicated in pathological conditions associated with inflammation including stroke and Alzheimer's disease (El Khoury et al, 2003;Febbraio et al, 2000;Kim et al, 2008). This receptor is expressed in many different cell types such as microglia, astrocytes, microvascular endothelial cells, monocytes/macrophages, and platelets (Bao et al, 2012). It has been reported that the activation of astrocytes may be regulated by the presence and function of these transporters (Glatz et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…In particular, CD36, a class B scavenger receptor, has been implicated in pathological conditions associated with inflammation including stroke and Alzheimer's disease (El Khoury et al, 2003;Febbraio et al, 2000;Kim et al, 2008). This receptor is expressed in many different cell types such as microglia, astrocytes, microvascular endothelial cells, monocytes/macrophages, and platelets (Bao et al, 2012). It has been reported that the activation of astrocytes may be regulated by the presence and function of these transporters (Glatz et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…However, it has been recently demonstrated that CD36 plays a pivotal role in astrocytic survival, and proliferation In fact, CD36 deficient and CD36 -siRNA treated animals had reduced astrogliosis and wound healing. Thus, it is now accepted that CD36 signaling intimately correlates with astroglial proliferation (Bao Y 2012).…”
Section: Central Nervous System Resident Cells and Strokementioning
confidence: 99%
“…During SCI, astrocytes perform proliferation, hypertrophy, and migration (Wu et al 2012;Yin et al 2012). Astrocytes that over-activated would result in formation of glial scar and secretion of multiple neurotoxic molecules which hold back the neuroregeneration after injury (Bao et al 2012). Our study indicated that injury-evoked PRDX1 was expressed in reactive astrocytes in rat spinal cord, while the previous research suggested that PRDX1 was not expressed in astrocytes of mouse brain (Jin et al 2005).…”
Section: Discussionmentioning
confidence: 98%